The Psychology of Slips - Sellen, Abigail; Norman, D. A. (Experimental Slips and Human Error, 1992)
I planned to lock my door but not to put the chain on. I locked the door and proceeded to put the chain on all the while thinking that it wasn’t what I wanted to do.